Macrobrachium tenuipes, a new stygophile freshwater prawn specie (Crustacea: Caridea: Palaemonidae) from a karst cave of Guangxi, southwestern China - Zhu, Xiao-Ping; Chen, Qing-Hua; Zheng, Xiao-Zhuang; Chen, Wen-Jian; Guo, Zhao-Liang (Zootaxa, 2020)
Based on morphological, molecular, and ecological evidences, a fourth species of cave-dwelling shrimp Macrobrachium tenuipes sp. nov. is described from Guangxi Zhuang Autonomous Region, southwestern China. This new species with smooth carapace and the extremely slender pereiopods, can be separated from other congeners by the shape of rostrum; the segmental ratios, the arrangement of teeth on the cutting edge of the fingers of second pereiopod; the longer and narrower scaphocerite; and the longer uropodal diaeresis spine. The new taxon is genetically distinct from 18 other species of Macrobrachium for which COI and 18S rRNA sequences are available. The data observed on the habitat and ecology will contribute to the conservation for M. tenuipes sp. nov.